THE EFFECT OF ANIMATED VIDEOS AS A MEDIUM FOR REDUCING PRE-OPERATIVE ANXIENTY WITH GENERAL ANESTHESIA - Anita Setyowati; Raden Sugeng Riyadi (Jurnal Kesehatan Kusuma Husada, 2025)
Background: Preoperative anxiety is a common emotional response in patients undergoing surgical procedures, including laparotomy with general anaesthesia. Effective preoperative education can be one strategy to reduce anxiety. Animated videos about the anaesthesia procedure can improve patients' understanding and reduce their anxiety about medical procedures. This study aimed to determine the effect of animated videos as an educational medium in reducing preoperative anxiety in laparotomy with general anaesthesia. Methods: This study used a quasi-experimental design with a pre-test and post-test approach with a control group. The sample consisted of 30 patients scheduled for laparotomy at PKU Muhammadiyah Gamping Hospital, divided into 2 groups. Anxiety was measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data was analyzed using the Mann-Whitney U Test.Results: This study shows that in the intervention group, the majority of respondents before watching the animated video had moderate anxiety levels, with 8 respondents (53.3%). After being given the animated video, the majority of respondents showed mild anxiety levels, with 6 respondents (40.0%). In the control group, the majority of respondents had moderate anxiety levels, with 8 respondents (53.3%). After being given nursing care from the hospital without being given the animated video, the majority of respondents showed mild anxiety levels, with 9 respondents (60.0%). Data analysis showed a significant decrease in anxiety scores in the intervention group compared to the control group (p < 0.05). Conclusion: The use of animated educational media is recommended as part of standard preoperative preparation in hospitals.